The effect of gestational weight gain on likelihood of referral to obstetric care for women eligible for primary, midwife-led care after antenatal booking. (March 2016) - Daemers, Darie O.A.; Wijnen, Hennie A.A.; van Limbeek, Evelien B.M.; Budé, Luc M.; Nieuwenhuijze, Marianne J.; Spaanderman, Marc E.A.; de Vries, Raymond G.
Abstract: Objective: to examine the effect of gestational weight gain (GWG) on likelihood of referral from midwife-led to obstetrician-led care during pregnancy and childbirth for women in primary care at the outset of their pregnancy. Design: secondary analysis of data from a prospective cohort study. Setting: Dutch midwife-led practices. Participants: a cohort of 1288 women of Northern European descent, with uncomplicated, singleton pregnancy at antenatal booking who consequently were eligible for primary, midwife-led care. Measurements: because of the absence of an established GWG guideline in the Netherlands, we compared the effect of inadequate and excessive GWG according to two GWG guidelines: the criterion traditionally used, which is based on knowledge of the physiological components of GWG, advising 10–15 kg as a normal GWG irrespective of a woman׳s BMI category, and the 2009 Institute of Medicine recommendations (IOMr) on GWG, which provide BMI related advice. Outcome measures were: number of women referred from midwife-led to obstetrician-led care during pregnancy and during childbirth; indications of referral and birth outcomes. Findings: GWG above traditional criteria (Tc; >15 kg between 12 and 36 weeks) was associated with increased odds for referral during childbirth (adjusted odds ratio (aOR) 1.88; 95% confidence interval (CI) 1.22–2.90), but had no effect on referral during pregnancy (aOR .86; 95% CI .57–1.30). No associations were established between GWG below Tc (<10 kg) and referral during pregnancy (aOR 1.08; 95% CI .78–1.50) or childbirth (aOR 1.08; 95% CI .74–1.56). No associations were found between GWG below and above the IOMr and referral during pregnancy (below IOMr: aOR 1.01; 95% CI .71–1.45; above IOMr: aOR .89; 95% CI .61–1.28) or childbirth (below IOMr: aOR .85; 95% CI .57–1.25; above IOMr: aOR 1.09; 95% CI .73–1.63). With regard to the effect of GWG according to both recommendations on indications for referral and birth outcomes, GWG above Tc was associated with higher rates of referral for hypertensive disorders (aOR 1.91; 95% CI 1.04–3.50) and for meconium stained liquor (aOR 2.22; CI 1.33–3.71) after adjusting for BMI and parity. Conclusions: GWG above Tc – irrespective of BMI category – was associated with doubled odds of referral to specialist care during childbirth. GWG below or above IOMR and GWG below TC were not associated with adverse obstetric outcomes in women who were eligible for primary care at the outset of their pregnancy. Implications for practice: weight gain <15 kg between 12 and 36 weeks is advised for women in all BMI categories in this population. It is important to validate GWG guidelines in a target population before implementing them. Highlights: In a primary care population GWG >15 kg increased odds of referral from midwife-led to obstetrician-led care during childbirth. GWG<10 kg may be acceptable in normal pregnancy and with healthy lifestyle. These findings concern all women irrespective of their BMI classification.